(untitled) (Editora Impacto Científico, 2025)
The penalty of banishment (degredo), systematically applied by the Portuguese Monarchy and codified by the Holy Office, operated on two fronts: as a mechanism of legal and spiritual exclusion of the undesired, and as a political strategy for the occupation and settlement of colonial territories. The exile of convicts to Brazil entailed not only the crossing of a physical ocean but also entry into a symbolic space of expiation, marginalization, and potential reintegration. Degredo was, by definition, an ambiguous punishment: both punitive and utilitarian, humiliating and hopeful, isolating and refunctionalizing. It transformed the convict into a liminal subject—somewhere between criminal and colonist, heretic and penitent - incorporating them functionally into the margins of the Empire. The long journey and the hardships of the Atlantic crossing heightened the experience of exile and penance, while also opening the possibility for redemption. By mitigating sentences and interceding for commutations, the Holy Office enacted a dual form of justice: disciplinary and spiritual, repressive and restorative. In this context, banishment reveals itself as a technology of power that articulates coercion and clemency, operating both as corporeal punishment and as spiritual pedagogy, in accordance with the inquisitorial ideal of correction and salvation.